1997
DOI: 10.1002/ceat.270200110
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of solids concentration by an ultrasonic transmission technique

Abstract: An ultrasonic transmission technique is under development to determine the concentration of solids in a three-phase slurry reactor by measuring the velocity of ultrasound in slurries. Preliminary measurements have been made on slurries consisting of water, glass beads, and air bubbles. The data show that both the sound speed and attenuation are well-defined functions of both the solid and gas concentrations in the slurries. A simple model is proposed to correlate the concentration of solids with the measured u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…It is found that the attenuation of the ultrasonic wave is a function of gas holdup (Macchi et al, 2001;Stolojanu and Prakash, 1997;Soong et al, 1997Soong et al, , 1999Warsito et al, 1999). All the documented ultrasonic measurement methods were developed based on phase difference of acoustic waves, transit time variation in sound signals, and change in amplitude of ultrasounds with certain simplifications and assumptions (Uchida et al, 1989a,b;Havlicek and Sovava, 1984;Tavlarides and Bonnet, 1988;Kirou et al, 1988a,b;Anson and Chivers, 1989;Macchi et al, 2001;Stolojanu and Prakash, 1997;Soong et al, 1995aSoong et al, ,b, 1997Soong et al, , 1999Fox et al, 1955;Warsito et al, 1999).…”
Section: Ultrasonic Technique In Multiphase Systems 631mentioning
confidence: 99%
“…It is found that the attenuation of the ultrasonic wave is a function of gas holdup (Macchi et al, 2001;Stolojanu and Prakash, 1997;Soong et al, 1997Soong et al, , 1999Warsito et al, 1999). All the documented ultrasonic measurement methods were developed based on phase difference of acoustic waves, transit time variation in sound signals, and change in amplitude of ultrasounds with certain simplifications and assumptions (Uchida et al, 1989a,b;Havlicek and Sovava, 1984;Tavlarides and Bonnet, 1988;Kirou et al, 1988a,b;Anson and Chivers, 1989;Macchi et al, 2001;Stolojanu and Prakash, 1997;Soong et al, 1995aSoong et al, ,b, 1997Soong et al, , 1999Fox et al, 1955;Warsito et al, 1999).…”
Section: Ultrasonic Technique In Multiphase Systems 631mentioning
confidence: 99%
“…The presence of particles in fluid-particle systems, attenuates the sound wave; the attenuation is increased with the particle concentration (Stakutis et al, (1955)). This is due to the impedance difference between the solid particles and the fluid (Soong et al, (1997)). The attenuation coefficient of sound(𝛼 𝑠 ) wave transmitted through a medium over length 𝑥 can be calculated by:…”
Section: Attenuationmentioning
confidence: 99%
“…The ultrasound speed is dependent on the density and compressibility of the medium and is affected by the presence of solid particles and gas bubbles within the flow (Kong et al, (2017)). According to the literature in liquid-solid flows both the wave transmission time and the amplitude ratio (the ratio of the received signal amplitude, 𝐴 𝑖 , to the transmitted signal amplitude, 𝐴 𝑜 ) decrease with increasing solid volume fraction (Soong et al, (1997), Jingyuan and Yong, ( 2016)). In addition, an increase in gas velocity increases the attenuation of the propagated wave.…”
Section: Solid Volume Fractionmentioning
confidence: 99%